Intraductal papillary mucinous neoplasm of the pancreas – epidemiology, risk factors, diagnosis, and management. (3rd August 2017) - Aronsson, Linus; Andersson, Roland; Ansari, Daniel
Abstract: Intraductal papillary mucinous neoplasm (IPMN) is one of the most common cystic neoplasms of the pancreas. It is a heterogeneous disease and can be divided into ductal types and morphological subtypes. The incidence of IPMN is increasing, likely due to the widespread use of cross-sectional imaging and a growing elderly population. IPMN poses an increasing demand on the health care system. Current guidelines provide indications for surgery and recommendations for surveillance, but management of IPMN is still challenging in routine clinical practice. In this article, we review current knowledge about IPMN and provide future directions for improving diagnosis and management.